Multicolor (Vis-NIR) mesoporous silica nanospheres linked with lanthanide complexes using 2-(5-bromothiophen)imidazo[4, 5-f][1, 10]phenanthroline for in vitro bioimaging. Issue 1 (6th November 2014) - Liu, Ying; Sun, Lining; Liu, Jinliang; Peng, Yu-Xin; Ge, Xiaoqian; Shi, Liyi; Huang, Wei
Abstract : Using the modified phenanthroline ligand, the multicolor mesoporous silica nanospheres linked with lanthanide complexes were synthesized and characterized, and the application for cell imaging has been studied. Abstract : A novel mesoporous nanosphere functionalized with 3-(aminopropyl)triethoxysilane (APTES) and 2-(5-bromothiophen)imidazo[4, 5- f ][1, 10]phenanthroline (5-Br-Tip) was synthesized (denoted as Tip-MSS). With the coordinating function of the 5-Br-Tip to lanthanide (Ln) ions, for the first time, LnL3 (5-Br-Tip) complexes were linked to the mesoporous nanospheres. The derived materials, named Ln-Tip-MSS (Ln = Eu, Tb, Sm, Nd, Yb), were characterized by Fourier-transform infrared (FT-IR) spectroscopy, TEM, XRD (wide-angle and small-angle), N2 adsorption/desorption analysis, and fluorescence spectroscopy. Upon excitation in the ligand absorption, the Ln-Tip-MSS nanomaterials show characteristic visible (Eu, Tb, Sm) and NIR (Sm, Nd, Yb) luminescence (multicolor emission covered from 450 nm to 1400 nm spectral region). Of importance is that, with low cytotoxicity and good biocompatibility given by the methyl thiazolyl tetrazolium (MTT) assay, the Eu-Tip-MSS was successfully applied to cell imaging in vitro based on the Eu 3+ luminescence (under 405 nm excitation).